SEMELFAKTIV FE'LLARNING LEXICON VA ASPEKTUAL TURKUMLARI - Ahmedova Husniya Muhiddinovna (Scholars Digest Publishing, 2023)
This thesis explores the aspectal class of semelfactive verbs in English under the auspices of the current literature expansion. Semelfative verbs are said to form a solitary form of repeated movements.